2012
DOI: 10.1104/pp.111.187518
|View full text |Cite
|
Sign up to set email alerts
|

CYP701A8: A Rice ent-Kaurene Oxidase Paralog Diverted to More Specialized Diterpenoid Metabolism    

Abstract: All higher plants contain an ent-kaurene oxidase (KO), as such a cytochrome P450 (CYP) 701 family member is required for gibberellin (GA) phytohormone biosynthesis. While gene expansion and functional diversification of GA-biosynthesis-derived diterpene synthases into more specialized metabolism has been demonstrated, no functionally divergent KO/CYP701 homologs have been previously identified. Rice (Oryza sativa) contains five CYP701A subfamily members in its genome, despite the fact that only one (OsKO2/CYP7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 46 publications
(59 reference statements)
3
102
0
Order By: Relevance
“…With the exception of the moss Physcomitrella, which lacks GA phytohormones, the product of CYP701A is further oxidized in higher land plants by a second P450 to GA 12 . In the genome of rice (O. sativa), five CYP701A subfamily members are found, while only one, CYP701A6, fulfils the vital function of ent-kaurene oxidation en route to GA phytohormones [44]. Additionally, the five P450s are organized in one genomic cluster of 115 kb on chromosome 6.…”
Section: The Cyp71 Clan: Cradle Of Monoterpenoid and Sesquiterpenoid mentioning
confidence: 99%
“…With the exception of the moss Physcomitrella, which lacks GA phytohormones, the product of CYP701A is further oxidized in higher land plants by a second P450 to GA 12 . In the genome of rice (O. sativa), five CYP701A subfamily members are found, while only one, CYP701A6, fulfils the vital function of ent-kaurene oxidation en route to GA phytohormones [44]. Additionally, the five P450s are organized in one genomic cluster of 115 kb on chromosome 6.…”
Section: The Cyp71 Clan: Cradle Of Monoterpenoid and Sesquiterpenoid mentioning
confidence: 99%
“…The ensuing diTPS products often undergo further structural modifications through the activity of P450 enzymes, as exemplified in rice by the P450-catalyzed formation of several bioactive diterpenoid metabolites (Swaminathan et al, 2009;Wang et al, 2011Wang et al, , 2012aWang et al, , 2012b. Comparatively, less was known about the complexity of maize diterpenoid biosynthesis.…”
mentioning
confidence: 99%
“…The difference between the activity exhibited by AtKO and OsKO2 may reflect their distinct evolutionary contexts. In particular, although Arabidopsis seems to be representative of the Brassicaceae plant family, which does not produce any more specialized LRDs, only GA, and contains just one CYP701 family member, rice is representative of the Poaceae plant family, where it has been indicated that more specialized LRDs arose early, with widespread retention (20), and rice contains a number of CYP701A subfamily members with distinct function (9)(10)(11). This presumably exerted differing selective pressures on these genes, which was examined by molecular phylogenetic analysis of all characterized members of the CYP701 family ( Fig.…”
Section: Resultsmentioning
confidence: 99%